Food Insecurity, Quality of Life, and Diet Optimization of Low Income University Students in Selangor, Malaysia - Rajikan, Roslee; Shin, Lee Hui; Abdul Hamid, Nurul Izzati; Elias, Siti Masitah (Jurnal Gizi dan Pangan, 2019)
This study aim to determine the relationship between food security with quality of life and nutritional status among low income students in a public university in Selangor, Malaysia. A cross-sectional survey was carried out on 108 low income students who were chosen by convenient sampling method. Students were interviewed using a structured questionnaire to obtain information on their sociodemographic characteristics, food security status, quality of life, anthropometric data, and dietary intake. Results showed that 69.4% of students were food insecure with 50% reported low food security and 19.4% with very low food security. For quality of life, students scored highest in social relationship domain (68.60±14.53) while lowest in physical health domain (53.87±10.42). There was no significant association between food security and quality of life, ethnic, age, family income, financial assistance, CGPA, and food expenditure (p>0.05). Majority of students (59.2%) had normal Body Mass Index (BMI), followed by 20.4% were overweight, 10.2% were obese, and 10.2% were underweight. Therewas no significant correlation between nutritional status with food security status (p>0.05). To estimate the minimum daily food expenditure to fulfil all nutrient requirements, an optimum diet model was created by using linear programming model. Result showed that the minimum price of one day menu for male and female student was USD 4.90 and USD 5.20 each. The cost was higher than their average food expenditure (USD 2.90), indicating that students in the university have to spend more money on food sold at the university cafeteria to fulfill their nutrient recommendation. Hence, relevant authorities should take appropriate initiatives so that the food insecurity problem among low income university students can be managed to improve their quality of life and nutritional status.